The Influence Of Green Accounting, Environmental Performance, And Corporate Risk On Financial Performance With Corporate Governance As A Moderating Variable - Hilda Nur Awaliah; Dirvi Surya Abbas; Imam Hidayat (UNIVED Press, 2025)
This research examines the relationship between financial performance, environmental performance, and corporate accounting via the lens of corporate governance as a moderating variable. Data was retrieved from the financial reports of manufacturing businesses listed on the Indonesian Efek Exchange (BEI) from 2019 to 2023. The study was conducted using a quantitative method using Eviews 12 for regression. Environmental performance does not have a substantial effect on financial success, according to the research results, but green accounting and business risk do. Evidence suggests that good company governance amplifies the impact of accounting and risk on financial performance without modifying the correlation between environmental performance and financial success. In order to improve financial performance, these results show that innovative accounting methods backed by solid governance and efficient risk management are crucial. This research makes a valuable contribution to our understanding of financial performance-influencing elements, especially in the context of advanced business and risk management.